Analisis Potensi Pajak Parkir Dalam Meningkatkan Penerimaan Pajak Daerah di Kabupaten Labuhanbatu Selatan - Sipahutar, Eliyana; Arif, Muhammad; Ahmad, Nurfadhilah (Universitas Labuhanbatu, 2024)
One of the Regional Tax revenue posts is from Parking Tax. Parking tax is not the same as parking levy. Parking tax is a tax on operators of off-road parking spaces, whether provided in connection with the main business or provided as a business, including the provision of storage space for motor vehicles. Taxes on the operation of parking lots are a potential sector for increasing parking tax revenues and the contribution made by parking lots can spur regional economic development. This research aims to find out the potential for parking taxes in South Labuhanbatu Regency in increasing regional taxes. This research uses qualitative research with a descriptive approach. The data collection technique used in this research was interviews and documentation. The research subjects were employees from the Regional Revenue Agency program, namely those in charge of the parking tax sub-section in South Labuhanbatu. This research used a descriptive qualitative approach. The results of existing research show that the realization of parking tax revenue with the highest or largest percentage achieved is in 2020. And the regional government of South Labuhanbatu district has the potential to increase parking tax revenue. There are several obstacles experienced by the Regional Tax and Retribution Management Agency (BPPRD) of South Labuhanbatu Regency, including a lack of awareness of parking taxpayers, apart from the fact that in the field the limited number of officers or government apparatus is not commensurate with the number of taxpayers being examined. . And the competence of the officers means the ability to master tax regulations, especially parking tax.